The Integrative Education: The Vision of Character Education Based on Al-Qur’an - Suriyadi Suriyadi; Ahmad Jamin; Musdizal Musdizal (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The purpose of this study was to explore and describe the vision of education according to the Al-Qur’an and then found its relevance to modern character education theory. This study used qualitative design by using library research and specifically used in the mawdhu'i interpretation approach. The study results have shown that the integration of educational goals was seen in the use of several terms in the Al-Qur’an related to education. Dhikr was integrated with thinking, integration of understanding (cognitive) by acting what is understood (affective and psychomotor), applying syar'i law was integrated with the purpose of its application, and integration of thinking about nature by acknowledging the power of Allah. The verse signs that indicate integration in educational goals indicate that the domains of educational goals could not be separated but as a whole. The implication in the formulation of goals should not separate the cognitive, affective, and psychomotor domains. Thoughts, exercise, and sports might be integrated and synergized.